Evolution of Hepatic Steatosis to Fibrosis and Adenoma Formation in Liver-Specific Growth Hormone Receptor Knockout Mice - Fan, Yong; Fang, Xin; Tajima, Asako; Geng, Xuehui; Ranganathan, Sarangarajan; Dong, Henry; Trucco, Massimo; Sperling, Mark A. (Frontiers in Endocrinology, 2014)
Background: Non-alcoholic fatty liver disease (NAFLD) is one of the most common forms of chronic liver diseases closely associated with obesity and insulin resistance; deficient growth hormone (GH) action in liver has been implicated as a mechanism. Here, we investigated the evolution of NAFLD in aged mice with liver-specific GHR deletion. Methods: We examined glucose tolerance, insulin responsiveness and lipid profiles in aged male mice (44-50 weeks) with GHRLD. We performed proteomics analysis, pathway-based Superarray assay, as well as quantitative RT-PCR to gain molecular insight into the mechanism(s) of GHR-deficiency mediated NAFLD. In addition, we examined the pathological changes of livers of aged GHRLD male mice. Results: The biochemical profile was consistent with that of the metabolic syndrome: abnormal glucose tolerance, impaired insulin secretion, and hyperlipidemia. RT-qPCR analysis of key markers of inflammation revealed a 3-5 fold increase in TNFα and CCL3, confirming the presence of inflammation. Expression of fibrotic markers (e.g., Col1A2 and Col3A1) was significantly increased, together with a 2-3 fold increase in TGFβ transcripts. Proteomics analyses showed a marked decrease of Mup1 and Selenbp2. In addition, pathway-analysis showed that the expression of cell cycle and growth relevant genes (i.e., Ccnd1, Socs2, Socs3 and Egfr) were markedly affected in GHRLD liver. Microscopic analyses (H&E) of GHRLD livers revealed the presence of hepatic adenomas of different stages of malignancy. Conclusion: Abrogation of GH-signaling in male liver leads to metabolic syndrome, hepatic steatosis, increased inflammation and fibrosis, and development of hepatic tumor. Since obesity, a common precursor of NAFLD, is a state of deficient GH secretion and action, the GHRLD model could be used to unravel the contribution of compromised hepatic GH-signaling in these pathological processes, and help to identify potential targets for intervention.